Alternating Current Electrolysis as Efficient Tool for the Direct Electrochemical Oxidation of Hydroxamic Acids for Acyl Nitroso Diels–Alder Reactions. Issue 37 (8th August 2021) - Fährmann, Jan; Hilt, Gerhard
Abstract: The acyl nitroso Diels–Alder reaction of 1, 3‐dienes with electrochemically oxidised hydroxamic acids is described. By using alternating current electrolysis, their typical electro‐induced decomposition could be suppressed in favour of the 1, 2‐oxazine cycloaddition products. The reaction was optimised using Design of Experiments (DoE) and a sensitivity test was conducted. A mixture of triethylamine/hexafluoroisopropanol served as supporting electrolyte in dichloromethane, thus giving products of high purity after evaporation of the volatiles without further purification. The optimised reaction conditions were applied to various 1, 3‐dienes and hydroxamic acids, giving up to 96 % isolated yield. Abstract : Hydroxamic acids were electrochemically oxidised to initiate acyl nitroso Diels–Alder reactions with 1, 3‐dienes. By using alternating current, their often encountered electrochemically induced decomposition could be suppressed to generate the desired cycloaddition products in up to 96 % yield. The optimisation of this reaction was performed using the Design of Experiments approach.